INVESTIGATING NITROGEN SOURCES FOR BACTERIAL CELLULOSE BASED VEGAN LEATHER - Bansal, Chehak; Sharma, Divyansha; Sisodia, Nidhi; Chanchal (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Background: A vegan alternative to leather is a novel concept, and substitutes are coming up from the most unlikely sources, like mushroom caps, pineapple, seaweed, etc. Bacterial cellulose is a leather-like material produced during the production of kombucha. The aim of the present study was to evaluate the proper conditions for the growth of bacterial cellulose and it’s after treatments for making vegan leather. Methods: For effective biosynthesis of bacterial cellulose, a sufficient amount of carbon and nitrogen is required. Tea, coffee, and dried orange peels were taken as nitrogen sources, while various concentrations of edible crystal sugar were taken as carbon sources and were evaluated to obtain the best results. After treatment of bacterial cellulosic layers was done using various methods, results were evaluated. After drying the bacterial cellulosic layer, vegan leather was obtained. Functional properties of vegan leather were tested as per industry standards and compared on the basis of various nitrogen sources used for production. Result and Conclusion: The present study indicated that vegan leather made from tea as a nitrogen source had the highest tensile strength, the lowest thickness, and very good water repellence. All three, tea, coffee, and sugar, can be used as good nitrogen sources for the propagation of bacterial cellulose. All of these could be used as economic as well as eco-friendly sources for making vegan leather.